2018
DOI: 10.1155/2018/3076806
|View full text |Cite
|
Sign up to set email alerts
|

ANCA-Associated Necrotizing Glomerulonephritis Overlapping with Mesangial Proliferative Lupus Nephritis Refractory to Plasmapheresis, Steroid Pulse Therapy, and a Combination of Mycophenolate Mofetil and Rituximab

Abstract: Necrotizing glomerulonephritis (GN) associated with antineutrophil cytoplasmic antibody (ANCA) has been increasingly recognized in the context of class III or IV lupus nephritis (LN), hereafter designated as ANCA-associated necrotizing LN. While this subset of GN appears to portend an unfavorable renal outcome, it is not clear whether it represents a distinct entity and benefits from a more aggressive therapy. We report a 78-year-old woman who presented with rapidly progressive GN and was found to have a doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Glucocorticoids receptors (GRs) belong to the family of steroid hormone receptors and they are found in a number of different cell types in the human kidney, including glomerulus cells, podocytes, epithelial cells and endothelial cells ( 1 , 2 ). Glucocorticoids (GCs) are commonly used to treat proteinuric glomerular diseases, such as membranoproliferative glomerulonephritis ( 3 ), membranous nephropathy ( 4 ), IgA nephropathy, crescentic glomerulonephritis ( 5 ) and antiglomerular basement membrane disease ( 6 ). In general, GCs remain the cornerstone of treatment for a number of inflammatory such as lupus nephritis (LN) ( 7 , 8 ) as well as for non-inflammatory renal diseases such as the Minimal Change Nephropathy (MCD) ( 7 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids receptors (GRs) belong to the family of steroid hormone receptors and they are found in a number of different cell types in the human kidney, including glomerulus cells, podocytes, epithelial cells and endothelial cells ( 1 , 2 ). Glucocorticoids (GCs) are commonly used to treat proteinuric glomerular diseases, such as membranoproliferative glomerulonephritis ( 3 ), membranous nephropathy ( 4 ), IgA nephropathy, crescentic glomerulonephritis ( 5 ) and antiglomerular basement membrane disease ( 6 ). In general, GCs remain the cornerstone of treatment for a number of inflammatory such as lupus nephritis (LN) ( 7 , 8 ) as well as for non-inflammatory renal diseases such as the Minimal Change Nephropathy (MCD) ( 7 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The extensive necrotic and pauci-immune glomerular inflammation observed in some patients with Class IV-S LN may be associated with ANCAs [5,6,[8][9][10]. Some studies have reported an association between this histopathologic phenotype and ANCA positivity [5,6,8,9,[11][12][13], but others found no association.…”
Section: Introductionmentioning
confidence: 99%
“…GR is widely expressed in the human kidney, including in the glomerulus (30), and GCs are used clinically in a variety of proteinuric glomerular diseases, including membranoproliferative glomerulonephritis (11), membranous nephropathy (2), IgA nephropathy (12), crescentic glomerulonephritis of many etiologies (14,20,23), and antiglomerular basement membrane disease (29). However, it is from the treatment of nephrotic syndrome (NS), both in pediatric and adult patients, for which GCs are a mainstay of therapy, that most of the current knowledge about GC effects on glomeruli and clinical practice patterns have evolved.…”
mentioning
confidence: 99%